Nationalism and economic development in modern Eurasia - Mosk, Carl. (Routledge explorations in economic history ;, 2013)
"This book advances a new theory of why nationalism emerged in the modern world. In particular it explains why nationalism and economic development are closely linked, and why warfare plays a crucial role in the spread of the nation-state system. It is based on qualitative and quantitative evidence over the period 1600 to 2000 for seven countries--Great Britain, France, Germany, Yugoslavia, the United States, Japan and China "--